A cross-sectional study applying the PRECEDE model to explore factors influencing epidemic prevention behaviors among preschool educators - Yi-Ying He; Wei-Hsiang Huang; Chen-Yin Tung (BMC Public Health)
Abstract Background This study investigates the epidemic prevention behaviors of preschool educators and the factors influencing these behaviors, applying the PRECEDE model as a framework for analysis. Methods A cross-sectional survey was conducted among 190 preschool educators from public and private institutions in Taipei City and New Taipei City. A 64-item self-developed questionnaire was used to assess epidemic prevention behaviors and their determinants. The instrument’s reliability was supported by internal consistency (Cronbach’s α ranging from 0.85 to 0.92), while its validity was confirmed through expert review, item analysis, and confirmatory factor analysis (CFA). Statistical analyses included hierarchical regression to examine the influence of predisposing, reinforcing, and enabling factors on behavior. Results The model explained 54% of the variance in epidemic prevention behaviors. Enabling factors had the strongest influence (β = 0.46, p < 0.001), followed by reinforcing factors (β = 0.15, p < 0.05) and predisposing attitudes (β = 0.14, p < 0.05). Background variables, such as age (β = 0.23, p < 0.001) and years of service, collectively explained 14% of the variance. Conclusion The findings underscore the critical role of institutional support and professional training in enhancing epidemic prevention practices among preschool educators. Recommendations include integrating disease prevention training into professional development initiatives.